Reviews. Issue 1 (1st March 2016) - Yorke, Christopher; Beaton, Belinda; Falconer, Emily; Fernandez, Jeff
GIFT AND ECONOMY: ETHICS, HOSPITALITY AND THE MARKET, ERIC R. SEVERSON (ED.) (2012) Newcastle upon Tyne: Cambridge Scholars Publishing, 220 pp., ISBN: 9781443833837, h/bk, £39.99ALEHOUSES AND GOOD FELLOWSHIP IN EARLY MODERN ENGLAND, MARK HAILWOOD (2014) Woodbridge: Boydell Press, x+253 pp., ISBN: 9781843839422, h/bk, £60TOURISM AND CITIZENSHIP: RIGHTS FREEDOMS AND RESPONSIBILITIES IN THE GLOBAL ORDER, RAOUL V. BIANCHI AND MARCUS L. STEPHENSON (2014) Abingdon: Routledge, xiv + 279 pp., ISBN: 9780415707381, p/bk, £26.99NATURALLY HEALTHY MEXICAN COOKING: AUTHENTIC RECIPES FOR DIETERS, DIABETICS AND ALL FOOD LOVERS, JIM PEYTON (2014) Austin, TX: University of Austin Press, 272 pp., ISBN: 9780292745490, p/bk, £24.95